Barriers to access to medicines for noncommunicable diseases for patients using the Brazilian Unified Health System (SUS) (Brazilian Journal of Pharmaceutical Sciences, 2022)
This paper investigates difficulties related to access to medicines in SUS and factors associated with the inability to obtain medicines in SUS by non-communicable chronic disease (NCCD) patients who used this source for health care. We analyzed data from the National Survey on Access, Use and Promotion of Rational Use of Medicines. First analysis included individuals aged 20 years and over, diagnosed with at least one NCCD, with indication of medicine treatment and follow up of this disease (s) with a physician from SUS, and who reported having obtained some of the medicines in use from the SUS. The difficulties of obtaining medicines from SUS were investigated based on dimensions of access to medicines. Among 5. 155 individuals investigated, 65. 4% were women, 40 years old or older and 54. 3% residents of the Southeast region of Brazil. Aspects related to availability and waiting time to obtain medicines were the most significant reported barriers to access to medicines. Regional differences were found in basically all dimensions of access and the low availability of medicines in SUS pharmacies was the main reason cited for their search in private pharmacies.